Analisis Kandungan Protein Kasar dan Serat Kasar Silase Pakan Komplit Berbahan Dasar Kombinasi Jerami Padi dan Daun Lamtoro Sebagai Pakan Ternak Ruminansia - Jamaluddin, Darmawan; Nurhaeda, Nurhaeda; Rasbawati, Rasbawati (Fakultas MIPA UNM, 2019)
Abstract. The purpose of this study was to determine the increase in protein content and decrease in crude fiber in complete feed silage based on rice straw and lamtoro leaves as ruminant feed. This study used a completely randomized design (CRD) with 4 treatment levels and 3 replications namely J0 = 100% rice straw (control), J1 = 60% rice straw and lamtoro leaves 40% J2 = 70% rice straw and lamtoro leaves 30% J3 = 80% rice straw and lamtoro leaves 20%. The results showed that the combination of rice straw and lamtoro leaves had a very significant effect on the value of crude protein and crude fiber in complete feed silage. The highest average to the lowest protein content was J1 (11.45), J2 is equal to (9.50), J3 is equal to (8.44), and J0 is equal to (6.60). The average value of the highest crude fiber content to the lowest is (35.19), J3 is equal to (33.82), J2 is equal to (32.35), and J1is equal to (30.55). From the results of the study it is known that the best treatment that can be recommended is J1 treatment with a combination of 60% rice straw and lamtoro leaves 40%. Keywords: coarse protein, coarse fiber, complete feed silage, lamtoro leaves and rice straw.